Validitas Modul Biologi Berbasis Kearifan Lokal - Yunita Wardianti; Ria Dwi Jayati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The research aims at producing a valid biology module with local wisdom-based to senior high school students of Lubuklinggau. The research used research and development design with local wisdom-based. The development of the module refered to four D model which was developed by Thiagarajan. The model consists of four stages, namely Define, Design, Develop, and Disseminate. However, the research was limited on the development stage, particularly on validation stage. The validity test on this stage was a theoretic validity, which is executed by the three experts. The validation included material validation, construction/media validation, and language validation. The result showed that the development met the validity criteria with material validity score 4,165; construction/media validity score 4,259; and language validity score 4,338 categorised to be 'very valid'. In conclusion, the biology module developed with local wisdom-based to senior high school students of Lubuklinggau was valid. Keywords: validity, biology module, local wisdom